LAK21: 11th International Learning Analytics and Knowledge Conference 2021
DOI: 10.1145/3448139.3448178
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Disruptive Talk in Student Chat-Based Discussion within Collaborative Game-Based Learning Environments

Abstract: Collaborative game-based learning environments offer significant promise for creating engaging group learning experiences. Online chat plays a pivotal role in these environments by providing students with a means to freely communicate during problem solving. These chat-based discussions and negotiations support the coordination of students' in-game learning activities. However, this freedom of expression comes with the possibility that some students might engage in undesirable communicative behavior. A key cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…Gamification is becoming a popular and innovative way to support both instructor and learner in the educational field with learning or behavioral challenges. Currently, [122,123] studied gamified e-quiz exercises in a formative assessment context. In this study, four different types of learning engagement (behavioral, emotional, cognitive, and agentic) are discussed for performing the assessment.…”
Section: Impact Of Assessment and Feedback On Students' Outcomesmentioning
confidence: 99%
“…Gamification is becoming a popular and innovative way to support both instructor and learner in the educational field with learning or behavioral challenges. Currently, [122,123] studied gamified e-quiz exercises in a formative assessment context. In this study, four different types of learning engagement (behavioral, emotional, cognitive, and agentic) are discussed for performing the assessment.…”
Section: Impact Of Assessment and Feedback On Students' Outcomesmentioning
confidence: 99%
“…Students' conversations can create disruption in collaborative learning environments, impeding collaborative learning processes. Recent research on bullying, off-task behavior, and disruptive talk in collaborative learning environments examined a range of word embedding techniques as well as a variety of classical machine learning and deep learning techniques (Carpenter et al, 2020;Nikiforos et al, 2020;Park et al, 2021). Nikiforos et al (2020) explored the automatic detection of aggressive behavior (i.e., bullying) in two K-12 computer-supported collaborative learning environments.…”
Section: Related Workmentioning
confidence: 99%
“…The empirical evaluations indicated that the LSTMbased off-task behavior detection model with BERT embeddings outperformed other baseline approaches. Park et al (2021) presented an LSTMbased disruptive talk detection framework in a multi-party dialogue dataset from a collaborative game-based learning environment, utilizing features from chat messages, a range of linguistic features, gender, and pre-test scores. While this work has the potential to improve learning experiences by detecting disruptions within collaborative learning settings, they disregard the unique characteristics of multi-party dialogues.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy that while CollabAssist currently provides feedback to reduce micromanagement, it is a robust and model-independent system that can provide feedback on other forms of collaborative behaviors. For example, future researchers can explore using CollabAssist to reduce off task behavior [6], bullying [55], disruptive talk [58], disputational talk [82] or exclusive language [83] during collaboration.…”
Section: Qualitative Evaluationmentioning
confidence: 99%